Răspunsuri

2014-11-04T11:18:07+02:00
(a+b+c):3=31⇒a+b+c=93

(a+b):2=21⇒a+b=42⇒a+b+c=93
                                     42+c=93
                                     c=93-42
                                     c=51
(b+c):2=40⇒b+c=80⇒b=80-c=80-51=29⇒b=29

a+b=42⇒a=42-b=42-29=13⇒a=13

verificare:(13+29+51):3=93:3=31
scuze.. dar de unde 42? :O
a+b+c )/3= 31
(a+b)/2= 21 rezulta ca a+b= 42
(b+c)/2= 40, rezulta ca b+c= 80
a+b+c= 31*3= 93
a= 93-b-c=93-80= 13
b= (a+b)-a= 42-13= 29
c=93-a-b= 93-42= 51
(13+29+51)/3= 93/3=31
asta?
da :)))